Prior pneumococcal vaccination improves in-hospital mortality among elderly population hospitalized due to community-acquired pneumonia - Seohyun Kim; Moon Jin Kim; Jun-Pyo Myong; Yun-Hee Lee; Bo Yeon Kim; Ahyoung Hwang; Gui Ok Kim; Sung Hwan Jeong; Hyoung Kyu Yoon; Tai Joon An; Jeong Uk Lim (BMC Pulmonary Medicine, 2024)
Abstract Background Pneumococcal vaccination is a preventive method to reduce pneumonia related mortality. However, real-world data on efficacy of the pneumococcal vaccine in reducing mortality is lacking, especially in elderly patients. This study was conducted to assess the effects of prior pneumococcal vaccination in elderly pneumonia patients. Methods The data was procured from the Health Insurance Review and Assessment and Quality Assessment database. Hospitalized patients who met the criteria of community-acquired pneumonia (CAP) were included and they were grouped according to vaccination state. Patients were aged ≥ 65 years and treated with beta-lactam, quinolone, or macrolide. Patients were excluded when treatment outcomes were unknown. Results A total of 4515 patients were evaluated, and 1609 (35.6%) of them were vaccinated prior to hospitalization. Mean age was 77.0 [71.0;82.0], 54.2% of them were male, and mean Charlson comorbidity index (CCI) was 3.0. The patients in the vaccinated group were younger than those in the unvaccinated group (76.0 vs. 78.0 years; P < 0.001), and showed higher in-hospital improvement (97.6 vs. 95.0%; P < 0.001) and lower 30-day mortality (2.6 vs. 5.3%; P < 0.001). After adjusting confounding factors such as age, gender, CURB score and CCI score, the vaccinated group demonstrated a significant reduction in 30-day mortality (hazard ratio [HR] 0.58, 95% confidence interval [CI] 0.41–0.81; P < 0.01) and in-hospital mortality (HR 0.53, 95% CI0.37–0.78; P < 0.001) compared to the unvaccinated group in multivariate analysis. Vaccinated group showed better 30-day survival than those in non-vaccinated group (log-rank test < 0.05). Conclusions Among elderly hospitalized CAP patients, prior pneumococcal vaccination was associated with improved in-hospital mortality and 30-day mortality.